Cancer risk in DM1 is sex-related and linked to miRNA-200/141 downregulation. (20th September 2016) - Fernández-Torrón, Roberto; García-Puga, Mikel; Emparanza, José-Ignacio; Maneiro, Miren; Cobo, Ana-María; Poza, Juan-José; Espinal, Juan-Bautista; Zulaica, Miren; Ruiz, Irune; Martorell, Loreto; Otaegui, David; Matheu, Ander; et al.
Abstract : Objective: Describe the incidence of cancer in a large cohort of patients with myotonic dystrophy type 1 (DM1) and to unravel the underlying molecular mechanisms. Methods: Standardized incidence ratios (SIRs) were calculated in the Gipuzkoa DM1 cohort (1985–2013), dividing observed numbers by expected numbers for all cancers combined and stratified by sex. An estimation of the expected incidence was achieved by multiplying the age- and sex-specific incidence rates from the Basque population cancer registry by the person-years observed in the study cohort. Large-scale gene expression of peripheral blood mononuclear cell samples derived from 10 individuals with DM1 (5 men, 5 women) and 10 healthy matched controls was analyzed by the Human Gene 1.0 ST Affymetrix microarray. Results: During 18, 796 person-years of follow-up, corresponding to 424 patients with DM1, we observed 70 cancers in 62 patients giving a 1.81-fold risk (95% confidence interval [CI] 1.37–2.36), which was stronger in women than in men. Ovary (SIR 8.33, 95% CI 1.72–24.31) and endometrium (SIR 6.86, 95% CI 2.23–16.02) in women and thyroid (SIR 23.33, 95% CI 9.38–48.08) and brain (SIR 9.80, 95% CI 3.18–22.88) in both sexes were tumor sites with significantly higher risks in DM1. There were differences in gene expression between healthy controls and patients with DM1 and between men and women with DM1; all patients with DM1 combined and female patients with DM1 displayed significant downregulation of the microRNA (miRNA)-200c/141 tumor suppressor family. Conclusions: Oncologic risk is increased in DM1, especially in women and for gynecologic, brain, and thyroid cancer. Expression of the miRNA-200/miRNA-141 tumor suppressor family is decreased in women with DM1.